?STUDIES ON THE LEACHING OF COPPER FROM COMPLEX COPPER ORES OF CHITRAL (Biological Sciences - PJSIR, 1998)
Mineralogical and chemical studies have indicated potential deposits of complex ores containing minerals of copper, zinc, lead and silver in Dir and Chitral District of Pakistan. Pressure and agitation leaching studies were carried out for the extraction of copper and associated metals under varying parameters by using H2S04 in complex copper ores (average 1.27% Cu), reported to occur in Kaldam Gol area, (District Chitral, NWFP, Pakistan). The maximum reeqvery of copper obtained at 100°C with 1.87M H2S04 and 0.5 M HN03 for 30 minutes stirring at atmospheric pressure was 35%. On the other hand the maximum recovery of copper with pressure leaching at the same condition at> than 70 atmosphere pressure wasdoubled i. e. 87%.The conditions for maximum recovery of copper by leaching are presented for these ores.